Negative Monetary Policy Rates and Portfolio Rebalancing : Evidence from Credit Register Data - Bottero, Margherita (IMF Working Papers; Working Paper ;, 2019)
We study negative interest rate policy (NIRP) exploiting ECB's NIRP introduction and administrative data from Italy, severely hit by the Eurozone crisis. NIRP has expansionary effects on credit supply-- -and hence the real economy---through a portfolio rebalancing channel. NIRP affects banks with higher ex-ante net short-term interbank positions or, more broadly, more liquid balance-sheets, not with higher retail deposits. NIRP-affected banks rebalance their portfolios from liquid assets to credit-especially to riskier and smaller firms-and cut loan rates, inducing sizable real effects. By shifting the entire yield curve downwards, NIRP differs from rate cuts just above the ZLB.